Cyclophosphamide and regional citrate anticoagulation: A sour combination?. (November 2017) - Hendra, Tim; Simon, Jonathan; Lowe, Alastair
We present a case of a woman in her 70 s, on cyclophosphamide for multiple myeloma, who was admitted to critical care with grade III acute kidney injury. Renal replacement therapy with regional citrate anticoagulation was commenced. Shortly thereafter her systemic-ionised calcium levels fell and remained stubbornly low until post-filter calcium return was doubled. Her total-to-ionised calcium ratio gradually increased and so, to avoid further accumulation of citrate, anticoagulation was changed to heparin. Cyclophosphamide, which accumulates in renal failure, is known to interfere with key enzymes involved in the tricarboxylic acid cycle. We postulate that cyclophosphamide interfered with her citrate metabolism, resulting in persistent systemic chelation of calcium.